Apply Euler's Identity
e^(itheta)=costheta+isintheta
e^(5/8pii)=cos(5/8pi)+isin(5/8pi)
e^(3/2pii)=cos(3/2pi)+isin(3/2pi)
cos2theta=2cos^2theta-1=1-2sin^2theta
costheta=sqrt((1+cos2theta)/2)
sintheta=sqrt((1-sin2theta)/2)
cos(5/8pi)=sqrt((1+cos(10/8pi)/2))
cos(10/8pi)=cos(5/4pi)=cos(pi+1/4pi)
=cospicos(1/4pi)-sin(pi)sin(1/4pi)
=-1*sqrt2/2-0
=-sqrt2/2
cos(5/8pi)=sqrt((1-sqrt2/2)/2)=(sqrt(2-sqrt2))/(2)
sin(5/8pi)=sqrt((1-sin(10/8pi)/2)
sin(10/8pi)=sin(5/4pi)=2*-sqrt2/2=-sqrt2
sin(5/8pi)=sqrt((1+sqrt2/2)/2)=1/2sqrt(2+sqrt2)
e^(3/2pii)=cos(3/2pi)+isin(3/2pi)=0-i
And finally,
e^(5/8pii)*e^(3/2pii)=((sqrt(2-sqrt2))/(2)+i1/2sqrt(2+sqrt2))*(-i)
=1/2(sqrt(2+sqrt2))-i1/2(sqrt(2-sqrt2))